Radioactive gold nanocluster (198-AuNCs) showed inhibitory effects on cancer cells lines - Shijin Xuan; Aline Oliveira da Silva de Barros; Rogério Chaffin Nunes; Eduardo Ricci-Junior; Ademir Xavier da Silva; Muhammad Sahid; Luciana Magalhaes Rebelo Alencar; Clenilton Costa dos Santos; Veronica Morandi; Frank Alexis; Surtaj H. Iram; Ralph Santos-Oliveira (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Cancer is a global epidemic disease responsible for over ten millions death worldwide. The early diagnosis and the precise treatment with reduced adverse reactions are the main goal worldwide. In this study, we produced, characterized and evaluated (in vitro) in three different cancer cell lines (protaste, breast and melanoma) a radioactive gold nanocluster (R-AuNC) (198Au25(Capt)18). The pharmacokinetics as the influence in the ABC transporter (MRP1 Efflux Transporter Protein) was also evaluated. The results showed that R-AuNC (198Au25(Capt)18) are capable to kill the cancer cells lines of protaste, breast and melanoma. The pharmacokinetics showed a fast clearance and great volume of distribution, confirming the use of R-AuNC as nanomedicine for cancer treatment. Finally, the ABC transporter assay corroborated that the R-AuNC (198Au25(Capt)18) has no risk of being pumped out of cells by this efflux transporter. The results validate the use of gold nanoparticles as therapeutic nanomedicine for cancer treatment.